1999
DOI: 10.1542/peds.103.4.738
|View full text |Cite
|
Sign up to set email alerts
|

Is Greater Continuity of Care Associated With Less Emergency Department Utilization?

Abstract: Greater COC with attending physicians in outpatient teaching clinics is associated with lower ED utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 21 publications
7
122
2
1
Order By: Relevance
“…45 Studies have suggested an association of superior COC with fewer ED visits in different populations with asthma. 23,26,30,41,46 Our findings are consistent with those reported in a previous study focusing on children. 41 That study indicated that 42.3% of children with asthma had high COC (COCI ϭ 1), and those with medium or low COC had a higher risk of asthma-related ED visits (odds ratio, 1.21 and 1.38, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…45 Studies have suggested an association of superior COC with fewer ED visits in different populations with asthma. 23,26,30,41,46 Our findings are consistent with those reported in a previous study focusing on children. 41 That study indicated that 42.3% of children with asthma had high COC (COCI ϭ 1), and those with medium or low COC had a higher risk of asthma-related ED visits (odds ratio, 1.21 and 1.38, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a previous study reported that children with asthma in Taiwan have a higher average COC score 41 than do those in America and Canada. 24,30 The continuous treatment of patients with asthma through inhaled medicine provides safe and effective long-term disease management. 45 Studies have suggested an association of superior COC with fewer ED visits in different populations with asthma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations